PENGARUH STRATEGI BISNIS, TRANSFER PRICING DAN KOMITE AUDIT TERHADAP TAX AVOIDANCE (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR CONSUMER NON CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2018-2022) - Jauharah, Dhiyah; Sanulika, Aris (Publika Citra Media, 2024)
This research aims to analyze and provide empirical evidence of the influence of business strategy, transfer pricing and audit committees on tax avoidance. This type of research uses a quantitative approach, an associative method using secondary data, namely in the form of financial reports. The population in this research is non-cyclical consumer goods industry sector companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The sampling technique in this research was purposive sampling and obtained research samples of 18 companies with a total of 90 research samples. The data analysis technique used in this research is panel data regression analysis using E-views software version 12. The results of this research show that business strategy, transfer pricing and the audit committee simultaneously influence tax avoidance. Partially, business strategy and transfer pricing have no effect on tax avoidance, while the audit committee has an effect on tax avoidance.